TRANSFORMING STUDENT PERCEPTIONS IN DIGITAL MARKETING: IMPACT ANALYSIS EDUCATIONAL SEMINAR - Afandi, Ahmad; Amalia, Alfi; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
In the rapidly evolving digital era, digital marketing has become important for business strategy and Education. Increased use of the Internet, changes in consumer behavior, personalization, targeting, and cost-effectiveness of digital marketing emphasize the need to integrate it into Education, especially for students. This research explores how digital marketing seminars can influence students' perceptions, which is important in preparing them for the digital job market. This research includes a literature review on the role of digital marketing in education and related studies that have demonstrated the importance of integrating digital marketing skills into university curricula. This study identifies the need to deepen understanding of the effectiveness of digital marketing education, particularly through seminar or workshop formats. The study used a quantitative approach with a descriptive survey design. The sample consisted of 46 University of Muhammadiyah North Sumatra students who attended a digital marketing seminar. Data were collected using Likert scale questionnaires and analyzed using statistical methods, including descriptive analysis and t-tests.The results showed a significant increase in students' knowledge and interest in digital marketing post-seminar. Students report an increased perception of the relevance of digital marketing in careers and demonstrate a better readiness to apply this knowledge professionally. These findings are consistent with previous studies, confirming that intensive seminars can improve students' understanding of digital marketing. The significant difference in increased interest and career relevance demonstrates the effectiveness of seminars in linking theory with practice. Digital marketing seminars have proven effective in increasing students' understanding, interest, and awareness of digital marketing. These results support the further integration of digital marketing education into the university curriculum to prepare students for the challenges of the digital world of work